Evidence‐based assessments of clinical actionability in the context of secondary findings: Updates from ClinGen's Actionability Working Group. Issue 11 (11th October 2018) - Webber, Elizabeth M.; Hunter, Jessica Ezzell; Biesecker, Leslie G.; Buchanan, Adam H.; Clarke, Elizabeth V.; Currey, Erin; Dagan‐Rosenfeld, Orit; Lee, Kristy; Lindor, Noralane M.; Martin, Christa Lese; Milosavljevic, Aleksandar; Mittendorf, Kathleen F.; et al.
Abstract: The use of genome‐scale sequencing allows for identification of genetic findings beyond the original indication for testing (secondary findings). The ClinGen Actionability Working Group's (AWG) protocol for evidence synthesis and semi‐quantitative metric scoring evaluates four domains of clinical actionability for potential secondary findings: severity and likelihood of the outcome, and effectiveness and nature of the intervention. As of February 2018, the AWG has scored 127 genes associated with 78 disorders (up‐to‐date topics/scores are available at www.clinicalgenome.org ). Scores across these disorders were assessed to compare genes/disorders recommended for return as secondary findings by the American College of Medical Genetics and Genomics (ACMG) with those not currently recommended. Disorders recommended by the ACMG scored higher on outcome‐related domains (severity and likelihood), but not on intervention‐related domains (effectiveness and nature of the intervention). Current practices indicate that return of secondary findings will expand beyond those currently recommended by the ACMG. The ClinGen AWG evidence reports and summary scores are not intended as classifications of actionability, rather they provide a resource to aid decision makers as they determine best practices regarding secondary findings. The ClinGen AWG is working with the ACMG Secondary Findings Committee to update future iterations of their secondary findings list. Abstract : ClinGen's Actionability Working Group (AWG) evaluates four domains of clinical actionability for potential secondary findings: severity and likelihood of the outcome, effectiveness and nature of the intervention. AWG scores were compared between genes/disorders recommended for return as secondary findings by the American College of Medical Genetics and Genomics (ACMG) with those not currently recommended (non‐ACMG). Disorders recommended by the ACMG scored higher on outcome‐related domains (greater severity and likelihood) but were not different for intervention domains (and effectiveness and nature).